2017
DOI: 10.1371/journal.pgen.1007050
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Xist RNA from the inactive X during B cell development is restored in a dynamic YY1-dependent two-step process in activated B cells

Abstract: X-chromosome inactivation (XCI) in female lymphocytes is uniquely regulated, as the inactive X (Xi) chromosome lacks localized Xist RNA and heterochromatin modifications. Epigenetic profiling reveals that Xist RNA is lost from the Xi at the pro-B cell stage and that additional heterochromatic modifications are gradually lost during B cell development. Activation of mature B cells restores Xist RNA and heterochromatin to the Xi in a dynamic two-step process that differs in timing and pattern, depending on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 76 publications
9
116
0
Order By: Relevance
“…epigenetic modifications on the Xi, but that Xist RNA and H3K27me3 simultaneously return to the Xi following in vitro activation (21,22). We also found that Xist RNA first disappears from the Xi at the pro-B cell stage of B cell development in BM and that heterochromatin marks are progressively lost from the Xi during B cell differentiation (23). Here, we characterized the Xist RNA and H3K27me3 enrichment on the Xi during T cell development in the thymus, and we examined the epigenetic features of the Xi in specific CD4 + T cell subsets, using in vitro and in vivo activation approaches.…”
Section: Introductionsupporting
confidence: 53%
“…epigenetic modifications on the Xi, but that Xist RNA and H3K27me3 simultaneously return to the Xi following in vitro activation (21,22). We also found that Xist RNA first disappears from the Xi at the pro-B cell stage of B cell development in BM and that heterochromatin marks are progressively lost from the Xi during B cell differentiation (23). Here, we characterized the Xist RNA and H3K27me3 enrichment on the Xi during T cell development in the thymus, and we examined the epigenetic features of the Xi in specific CD4 + T cell subsets, using in vitro and in vivo activation approaches.…”
Section: Introductionsupporting
confidence: 53%
“…Interestingly, the autosomally encoded ubiquitous transcription factor Yy1, which is essential for initiation and maintenance of Xist expression (Figure 5a), binds to a highly conserved cluster of binding sites in the 5′ region of Xist and also to Tsix . [ 80–83 ] While Yy1 is bound to all X chromosomes before XCI, its binding becomes restricted to the Xist‐expressing alleles at the onset of XCI (Figure 5b, red square). [ 81,82 ] Two related transcription factors, Rex1 and Yy2, were derived from Yy1 through retrotransposition in placental mammals and have similar binding motifs.…”
Section: Candidate Regulators and Mechanismsmentioning
confidence: 99%
“…Long non‐coding RNAs, a subset of non‐coding transcripts with more than 200 nucleotides in length, have been shown to play important roles in numerous biological processes, for example inflammation, immunity and various cancers . With the development of high throughput RNA sequencing approach, a variety of novel lncRNAs were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs, a subset of non-coding transcripts with more than 200 nucleotides in length, have been shown to play important roles in numerous biological processes, for example inflammation, immunity and various cancers. [22][23][24][25] With the development of high throughput RNA sequencing approach, a variety of novel lncRNAs were identified. However, due to the tissue specific and low expression properties, functional involvement of a majority of lncRNAs remains unclear, up to date.…”
mentioning
confidence: 99%